Implementasi Integrasi Kurikulum Sekolah dan Kurikulum Pesantren di SDIT VIP Al-Huda - Fidianingsih, Yeni; Kartika, Nadia Raifah Nawa (IAINU Kebumen, 2024)
This study aims to determine the background and implementation of the integration of school curriculum and pesantren curriculum at SDIT VIP Al-Huda. This research is a type of qualitative research, taking the background of SDIT VIP Al-Huda. Data collection was taken by observation, in-depth interviews and documentation. Data validity analysis is carried out by triangulation techniques Data analysis is carried out by selecting and compiling the data obtained, then processed and analyzed so that conclusions can be drawn. The results of this study are: 1. The background of the use of the integration of school curriculum and pesantren curriculum at SDIT VIP Al-Huda, namely facing a moral crisis and westernized Indonesian society and religious materials in public schools are very minimal. 2. Implementation of school curriculum and pesantren curriculum at SDIT VIP Al-Huda, namely: a) teachers analyze the material then determine learning methods b) Implementation of learning methods, namely the principal and waka curriculum and the foundation monitors all teacher performance. c) Evaluation of the learning methods of the foundation and the principal will evaluate based on what has been controlled and supervised together. d) Follow-up problems related to learning methods, namely the existence of a shift system, curriculum waka and the principal evaluates learning tools, learning methods, schedules, synchronizes time, receives input, creates a conducive work situation, provides teacher learning resources and facilitates all teacher needs, and familiarizes a culture of discipline.